2023
DOI: 10.3390/geosciences13050137
|View full text |Cite
|
Sign up to set email alerts
|

Critical Failure Factors of Flood Early Warning and Response Systems (FEWRS): A Structured Literature Review and Interpretive Structural Modelling (ISM) Analysis

Abstract: Flood warning and response systems are essential components of risk reduction strategies with the potential to reduce loss of life and impact on personal assets. However, recent flood incidents have caused significant loss of human lives due to failures in current flood warning and response mechanisms. These failures are broadly related to policies concerning, and governance aspects within, warning generation, the behaviour of communities in responding to early warnings, and weaknesses in associated tools and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Emotions such as fear, uncertainty, and concern are important intermediaries in the relationship between cognizance and safeguarding measures [76,82]. Indeed, several studies have reported a correlation between a lack of awareness regarding floods and a limited uptake of measures aimed at flood protection and preparedness [65,83]. Generally, measures are implemented by considering elevating homes, acquiring flood insurance, accumulating supplies, relocating building contents to higher floors, and carrying out evacuations.…”
Section: Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotions such as fear, uncertainty, and concern are important intermediaries in the relationship between cognizance and safeguarding measures [76,82]. Indeed, several studies have reported a correlation between a lack of awareness regarding floods and a limited uptake of measures aimed at flood protection and preparedness [65,83]. Generally, measures are implemented by considering elevating homes, acquiring flood insurance, accumulating supplies, relocating building contents to higher floors, and carrying out evacuations.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…A proactive approach involves diverting runoff water to potential flood pocket zones, which can act as natural storage areas, helping protect cities and communities from the brunt of flood impacts. By employing a combination of infrastructure development, strategic planning, and proper drainage management, disaster management plans can enhance flood resilience and minimize the devastating consequences of flooding events on vulnerable populations [83].…”
Section: Disaster Management Plansmentioning
confidence: 99%